PELATIHAN PEMBUATAN VIRGIN COCONUT OIL (VCO) SECARA FERMENTASI DI DESA BELOTAN, BENDO, MAGETAN - Retno, Raras Setyo; Pujiati, Pujiati; Utami, Sri (Jurnal Terapan Abdimas, 2016)
VCO(Virgin Coconut Oil) isderivedfrom the old fresh fruit ofthe oilpalm(Cocosnucifera). VCOis apurecoconutoilthat resistant to heat, light, oxygenanddegradationprocess, becauseits chemical structurecontains nodouble bonds. Other characteristics of theVCOis to have aclearcolor, softaromaanddelicious taste. VCO can be process with physical, chemicalandbiological technique. Inbiology, the process of makingthe VCOis donethroughfermentationtechniquesthatusing yeastSaccharomycescereviseae. The manybenefits andbusiness opportunitiesof VCO, makingmanypeople tostart a businessinthisfield.BelotanVillage, District BendoMagetanisone of the villagesthat have the potentialtodoand to develop the VCO business because inthevillagemanylocaloil plantsthathave  not  beenutilizedas  well  as  possible.  The  aim  ofthiscommunity  serviceis(1) I n t r o d u c i n g t h e   s i m p l e t e c h n o l o g y t o   m a k i n g V C O ,   ( 2 )   P r o v i d e g u i d a n c e t o t h e publicthatverymanybenefitsofVCO(3) Providea discourseon the establishment ofsmall businessesVCOandmarketing managementtothesevillagecommunities